TINJAUAN YURIDIS TERHADAP PELANGGARAN MEROKOK SAAT BERKENDARA BERDASARKAN UNDANG-UNDANG NO. 22 TAHUN 2009 - Widiantoro Widiantoro; Samuji (INTELIGENSIA MEDIA, 2023)
The aim of the research is to find out whether smoking while driving can be categorized as a traffic violation, to find out the sanctions for smoking while driving. The method uses normative juridical. The research results show that smoking while driving can be categorized as a traffic violation based on Article 283 Number 22 of 2009 concerning Road Traffic and Transportation, punishable by a maximum imprisonment of three months or a maximum fine of Rp. 750,000. Prohibiting smoking while driving violates Law no. 22 of 2009 concerning Road Traffic and Transportation because of the smoking activity of course the driver must divide his concentration and be able to be distracted, this is due to the presence of two physical activities simultaneously so that the chance of an accident occurring on the road becomes greater. Minister of Transportation Regulation No. 12 of 2019 article 6 letter c states that drivers are prohibited from smoking and carrying out other activities that disturb concentration while riding a motorbike.